The Problem of Subjectivity in Algorithmic Creativity Organisation - Tetiana Sovhyra (Культура і мистецтво у сучасному світі, 2024)
The aim of the article is to study the issue of determining subjectivity, authorship and uniqueness of the results of producing the creative process, organised by the use of algorithmic calculations. Results. The article clarifies the possibility of organising the artistic and creative process using mathematical calculations, and automating the reproduction of certain manipulations, additionally, it reveals signs of the uniqueness of the corresponding generation results, and grounds the degree of automating the cultural process. The scientific novelty of the article is revealed in the process of highlighting technical assets of modern art, which, although slowly, nevertheless quite demonstratively show the potential of algorithmic computing as a stimulator of creative innovations. Among the methods used in the process of analysing the issues which are raised in the article, first of all, the analytical method has to be singled out, that is based on both historical and philosophical processes, as well as modern cultural activity. Conclusions. It is revealed that algorithmic creativity is actually a kind of mechanised production process, organised in accordance with the features of machine training, and the identified signs of stylistic imitation of traditional practices. Two types of practices for organising the corresponding creative process are established according to the degree of interaction of artists with robotic systems: practices where robotic mechanisms become “subjects of creativity”, that is they are able to produce content for organizing artistic processes; practices involving the equal interaction of robotic mechanisms and artists (for instance, in theatrical performances). The cultural process automation leads to the decrease in the artist’s participation, and weakening of his authorship, but he still has an absolute advantage in the thinking orientation. Interpretation of meaningful content is a critical problem in relevant practices. The usage of algorithms in creating art products challenges traditional methods of artistic cultural creation, as the artist’s meaning and intentions are not always clear. Evaluating further prospects for the artistic culture development requires taking into account these aspects, and recognising potential consequences of forming algorithmic creativity for the further cultural development of humanity.